The Rough Guide to Belgium & Luxembourg : best beers, historic cities, outstanding art. - Lee, Phil, ....-; Dunford, Martin, ....- (London : Rough Guides, 2011)
The Rough Guide to Belgium and Luxembourg is the ultimate guide to these fascinating countries. The guide is packed with reviews of the wonderful art galleries and historic sights of Ghent, Bruges, Antwerp and Brussels, and provides you with the best information for getting around, whether you want to explore the forests of Ardennes by bike or take a historical walk. The guide also gives you the low-down on Belgium's best beers, hotels and restaurants. There's also full practical information on where to drink, sleep, party and eat, whatever your budget. The guide lays bare all the most surprising aspects of both countries, with accurate maps and detailed information helping you to get under the skin of Belgium and Luxembourg, whilst stunning photography and a full-colour introduction make this your ultimate travelling companion.
Keywords: België -- Reisgidsen; Luxemburg (groothertogdom) -- Reisgidsen